Islamic Education in the Digital Age: Students' Perspectives on the Vark Model in the Context of Education 4.0 - Siregar, Hariman Surya; Rizza, Muhamad; Nurhamzah, Nurhamzah (Ulumuna, 2025)
In order to better understand how students' learning styles affect their engagement with course contents, this study looks at how the VARK (Visual, Auditory, Read/Write, Kinesthetic) learning paradigm is applied in Islamic education. The study's two primary aims are first to examine how well students believe their preferred learning methods align with traditional versus digital learning environments and then to investigate how these preferences affect their interaction with Islamic educational materials. The study employs a semi-structured interview guide to record individual experiences during in-depth interviews conducted with 15 University of Utara Malaysia (UUM) students, utilizing a qualitative research approach. Within UUM's Islamic curriculum, a thematic analysis is conducted to identify trends, obstacles, and benefits associated with each VARK learning style. Specific obstacles include the dense structure of classical books for read/write learners, the monotony of audio materials, information overload for visual learners, and a lack of kinesthetic learning possibilities. The findings underscore the importance of an integrated, adaptable curriculum that accommodates diverse learning styles, thereby increasing student engagement and academic achievement. This study contributes to the literature on Islamic education by offering curriculum design recommendations that align with students' learning preferences, thereby facilitating the transition to Education 4.0.